Workplace democracy and psychological capital: a paradigm shift in workplace - Han, Ki-Soon; Garg, Pooja (Management research news, 2018)
Purpose This paper aims to explore the role of workplace democracy in generating psychological capital, which is an inevitable paradigm for the contemporary organizations. The study also provides a conceptual framework which connotes the nexus between the two constructs. Design/methodology/approach The study is qualitative in nature and uses content analysis to identify the determinants of workplace democracy and psychological capital. Furthermore, the study used SPSS macro, i.e. PROCESS, a computational tool for calculating inter-coder reliability by using KALPHA, i.e. Krippendorff’s alpha reliability estimate (Hayes, 2013; Krippendorff, 2011). Findings The present study adds to the literature by signaling the dire need for building democratic workplaces and offers significant insights for the management and human resource practitioners to cultivate workplace democracy to build their employees’ psychological strengths, which in turn will result in enhanced organizational outcomes. Originality/value The present study brings attention toward the necessity for a shift in the generic organizational strategies and instigate organizations to nurture a democratic setup for developing employees’ psychological capital.